The situation of Ukrainean refugees as perceived by the teenagers from Dobrogea, in a post-pandemic context - Stănescu, Nina; Dan, Adrian; Tasențe, Tănase (Technium Social Sciences Journal, 2023)
This study explores changes in attitude and coping strategies to some pressures and stressors generated by global social problems, felt at the individual level. The aim of the study was to identify how teenagers / civil society perceive the (difficult) situation that refugees are going through, and how they (teenagers) have adapted to the new reality and design ways out of the crisis in case of would face a similar problem. The specific objectives of the study are 1) how civil society adapted to the pandemic; 2) how civil society adapted to the wave of refugees following the war. The study took place between March 1-15, 2022 and targeted the Dobrogea area, especially Constanţa county.